(untitled) (Baghdad Science Journal, 2007)
This study was carried out to find out the effect of germination of broad beans and chickpeas seeds for different periods on their antinutritional factors content ( Trypsin inhibitor and Phytic acid ) and the chemical constituents of germination seeds compared with the control samples (ungerminated seeds) . The results indicated asignificant increase (P